Profiles of perfectionism, motivation, and self-evaluations among dancers: An extended analysis of Cumming and Duda (2012) - Quested, Eleanor; Cumming, J.; Duda, J. (Edizioni Luigi Pozzi s.r.l., 2014)
The 2×2 model posits that different combinations of evaluative concerns and personal standards perfectionism contribute to four distinct perfectionism subtypes (or profiles). This study provides further analysis of data from the only study to date to test this model in dance (Cumming & Duda, 2012). In doing so, we aimed to further examine the hypothesis proposed by Gaudreau and Thompson (2010) that mixed perfectionism is more adaptive than pure evaluative concerns perfectionism on account of the personal standards perfectionism dimensions that contribute to the mixed perfectionism profile. We also examined whether the model could explain differences in previously unexamined motivation-related constructs (intrinsic motivation and fear of failure) and indicators of self-evaluations (self-esteem and body dissatisfaction) between these and the other subtypes. 194 vocational dancers (169 female, 25 male, M age=16.73, SD=1.45) completed three subscales of the multidimensional perfectionism scale (Frost, Marten, Lahart, & Rosenblate, 1990) tapping the perfectionism dimensions of personal standards, concern over mistakes and doubts about actions. Dancers also responded to items assessing intrinsic motivation, fear of failure, self-esteem and body dissatisfaction. Differences between the four clusters established in Cumming and Duda (2012) in the criterion variables were revealed. Overall, findings provided partial support for each of the four hypotheses of the 2×2 model. Findings did not support the suggestion that personal standards perfectionism buffers mixed perfectionists from the debilitating consequences of evaluative concerns perfectionism.